Detection of Human Immunoglobulin G at Physiological Conditions with Chemically Functionalizated Carbon Nanotube Field Effect Transistors - Cid, Cristina C.; Riu, Jordi; Maroto, Alicia; Rius, F. X. (Current Nanoscience, 2008)
In this paper we report a label-free biosensor able to detect 10 mg/L of human immunoglobulin G (HIgG) at physiological conditions. It is based on a field effect transistor in which a network of carbon nanotubes (CNTs) acts as the conductor channel. HIgG antibodies are linked to the CNTs in three steps. First, the polymer polyethyleneimine (PEI) covers the CNTs'surface preventing the nonspecific binding of proteins. Second, the HIgG antibodies are linked to the CNTs using glutaraldehyde as a cross-linker. Finally, glycine is used to block the unreacted aldehyde groups and minimize unspecific adsorption effects. The selectivity of the sensor has been tested against 10 mg/L of serum albumin, the most abundant protein in plasma.
Keywords: human immunoglobulin G